Pilates conditioning for weight loss [videorecording (DVD)] - Deason, Suzanne (Gaiam, 2002)
Includes the complete 60-minute Pilates conditioning workout, two 45-minute workout variations to allow you to progress to the next level, and additional on-screen instruction with our exclusive exercise guide.